Effect of hopelessness on the links between psychiatric symptoms and suicidality in a vulnerable population at risk of suicide. Issue 2 (15th December 2015) - Gooding, Patricia; Tarrier, Nicholas; Dunn, Graham; Shaw, Jennifer; Awenat, Yvonne; Ulph, Fiona; Pratt, Daniel
Abstract: The aim of this study was to examine the impact of two risk factors working together on a measure of suicide probability in a highly vulnerable group who were male prisoners identified as being at risk of self harm. The first risk factor was psychiatric symptoms, including general psychiatric symptoms and symptoms of personality disorder. The second risk factor was psychological precursors of suicidal thoughts and behaviours which were defeat, entrapment, and hopelessness. Sixty-five male prisoners from a high secure prison in NW England, UK, were recruited, all of whom were considered at risk of suicide by prison staff. General psychiatric symptoms and symptoms of personality disorders predicted the probability of suicide. Hopelessness amplified the strength of the positive relationship between general psychiatric symptoms and suicide probability. These amplification effects acted most strongly on suicidal ideation as opposed to negative self evaluations or hostility. In contrast, defeat, entrapment and hopelessness did not affect the relationship between personality disorders and suicide probability. Clinical assessments of highly vulnerable individuals, as exemplified by prisoners, should include measures of a range of general psychiatric symptoms, together with measures of psychological components, in particular perceptions of hopelessness. Highlights: Suicide in prisoners is a global problem. Psychiatric disorders predict suicidality in high risk populations such as prisoners. Hopelessness amplifies effects of psychiatric illness on suicidality in prisoners. Hopelessness heightens the relationship between psychiatric symptoms and ideation. Reducing hopelessness is key to suicide prevention strategies in prisoners.